A Compact Dual-Band Metasurface-Based Antenna for Wearable Medical Body-Area Network Devices. (1st August 2020) - Mu, Guangchen; Ren, Pengshan
Abstract : A compact, low-profile wearable antenna capable of operation within the 5.1–5.46 GHz and 5.7–5.85 GHz medical body-area network band is suggested to make the antenna better for wearable devices. The integrated metasurface (MSs) antenna consists of as few as array of three wan-shaped components, directly below the planar waveguide-fed monopole antenna. The measurement of the integrated antenna is 0.56 λ 0 × 0.56 λ 0 × 0.08 λ 0, all while achieving an average gain of 8.2 dBi in working frequency and a front-to-back ratio (FB) in excess of 19 dB. As demonstrated by in-depth examination, the antenna performs exceptionally well in withstanding the distortion of structure, far superior to planar monopole antenna. Additionally, the metasurface enables the specific absorption rate (SAR) low to 0.84 W/kg, which makes this type of antenna suited to application in different wearable devices.